Edukasi Bahaya Rokok Kepada Siswa SMAN 1 Krueng Barona Jaya Kabupaten Aceh Besar - Syukriadi Syukriadi; Rawi Juwanda; Safrina Safrina; Depi Paramida; Riza Ul Fahmi (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
According to World Health Organization (WHO), about 1.3 billion people in the world were active smokers in 2020. Smoking causes more than 8 million deaths each year, of which about 1.2 million are victims who do not smoke, but are exposed to secondhand smoke. Children and adolescents are a group that is very vulnerable to the dangers of smoking. The WHO notes that about 90% of adult smokers start smoking before the age of 18. The methods used in this socialization are the lecture and question and answer method, then questionnaires are distributed before and after counseling to find out adolescents' understanding of the dangers of cigarettes. The suggestion for this activity is that students of SMAN 1 Krueng Barona Jaya, Aceh Besar Regency. This socialization activity was carried out for 1 hour. The result obtained from this socialization activity was that there was a change in students' understanding of cigarettes, in this activity was also attended by the Principal, Dewa teachers and students as many as 30 people. It will be held on Thursday, November 7, 2024 at the Hall of SMAN 1 Krueng Barona Jaya, at 09:00 WIB. This socialization activity was carried out by lecturers and students of Diploma Three Nursing.